Strategy To Support SDGs: Spatial Analysis of Digital Transformation and Regional Government Competition on Green Development Efficiency in East Java - Moh Najikhul Fajri (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2023)
This study aims to analyze the effect of digital transformation and local government competition on green development efficiency. This study uses panel data of 38 districts/cities in East Java during 2015-2022. This study uses slack-based measurement efficiency analysis and geography-weighted panel regression: spatial durbin model. The results show that in general, East Java has not yet reached the absolute level of technical efficiency. Meanwhile, specifically, digital transformation has a positive effect on green development efficiency. Meanwhile, local government competition does not lead to green development efficiency. The decline in green development efficiency is driven by internet penetration without government moderation and agriculture-oriented regions. Interestingly, this increase in green development efficiency induces positive spillovers for surrounding regions. The implications of this study include the need for further elaboration and exploration related to efforts to encourage input productivity. On the other hand, comprehensive mitigation from the central and local governments related to digital transformation, especially the use of the internet. Thus, green development efficiency can be achieved optimally.